2021
DOI: 10.1108/jmtm-12-2020-0488
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adoption of critical success factors for lean six sigma implementation

Abstract: PurposeThe objective of the study is to design and validate an instrument that allows organizations to assess their status regarding the adoption of the critical success factors (CSFs) that enable lean six sigma (LSS) implementation in order to achieve the expected benefits.Design/methodology/approachAn extensive literature review was conducted to define the LSS CSFs that have to be considered for the development of the questionnaire that would later be applied across all manufacturing companies on the Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Organizational management is needed as a guideline for the implementation of work, this is considered to have significant implications for both large and small companies. The absence of guidelines will make organizational actors lack standard guidelines in carrying out all existing work operations, so that work behavior tends to use volatile assumptions with the influence of surrounding conditions (Gastelum-Acosta et al, 2022). The measurement results shown in table 4 above show that the internal organization system is still very low (8%).…”
Section: Stage 1: Definementioning
confidence: 99%
“…Organizational management is needed as a guideline for the implementation of work, this is considered to have significant implications for both large and small companies. The absence of guidelines will make organizational actors lack standard guidelines in carrying out all existing work operations, so that work behavior tends to use volatile assumptions with the influence of surrounding conditions (Gastelum-Acosta et al, 2022). The measurement results shown in table 4 above show that the internal organization system is still very low (8%).…”
Section: Stage 1: Definementioning
confidence: 99%
“…(2021) identified 20 success variables crucial to the success of LSS, while highlighted the selection of competent personnel and top management commitment as primary CSFs [22]. Gastelum-Acosta et al ( 2022) identified nine CSFs, finding a substantial relationship between these criteria and the success of LSS programs [23]. Francescatto et al ( 2022) identified leadership, management involvement, project management, organizational structure, and effective communication with leaders and managers as key CSFs for successful LSS implementation [24].…”
Section: Critical Success Factors Of Lean Six Sigmamentioning
confidence: 99%
“…CSFs for LSS are widely researched (Gastelum-Acosta et al, 2022;Pathiratne et al, 2018;Raval et al, 2018;Yadav et al, 2021a). The hierarchy of CSF for LSS in Industry 4.0/Quality 4.0 is also established (Yadav et al, 2021b).…”
Section: Theoretical Background and Hypotheses Framingmentioning
confidence: 99%
“…The role of these stakeholders in LSS is crucial as cited in previous research. Top management commitment and employee involvement are two well-established critical success factors (CSFs) for LSS (Gastelum-Acosta et al. , 2022; Pathiratne et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation